Geochemical assessment of fluoride enriched groundwater and health implications from a part of Yavtmal District, India - Marghade, Deepali; Malpe, Deepak B.; Subba Rao, N.; Sunitha, B. (Human and ecological risk assessment, 2020)
A comprehensive study was conducted from a semi-arid part of Yavtmal District, Maharashtra, India through combination approaches of geochemical modeling and its health consequences. The groundwater quality assessment shows that 55% of groundwater samples have the concentration of fluoride above the desirable limit. The high Na + /Ca + ratio (>1.0) suggest the occurrence of cation exchange, which is further supported by Scholler' chloro-alkaline indices. The geochemical modeling reveals that the existence of CaCO 3 precipitation and CaF 2 in groundwater. Simulation analysis indicates the dissolution of calcite, gypsum, and albite and precipitation of dolomite, fluorite, halite, and K-feldspar along with cation exchange as the main water-rock interactions influencing the groundwater chemistry. This is further significantly supported by pollution index of groundwater (PIG). PIG indicates about 18% of total samples fall in very high pollution zone, 3% in high pollution zone, 8% in moderate pollution zone, 24% in low pollution zone, and remaining (47%) express insignificant pollution. The 28% of subject studied have skeletal fluorosis varying from mild to severe type. In different pollution zones, the affected persons by dental fluorosis are varying from 15% to 41%. A proper monitoring and treatment are required for high fluoride water before its use for drinking and cooking.